Adillatu al-Nahw Fi Syarh Kitab al-Kawakib al-Durriyyah 'Ala Mutammamah al-Ajrumiyah wa Atsar Isti'maluha 'Ala Fahm al-Qowaid al-Nahwiyah - Asrina, Asrina; Lubis, Arbonas (Arabiyatuna : Jurnal Bahasa Arab, 2019)
The objectives of this study were to find out the syntax evidence (adillah al-nahwu) in the book Syarh Kitab al-Kawakib al-durriyah ?ala Mutamammimah al-Ajrumiyyah, how to use the evidence of syntax (adillah al-nahwu) in it?s book, and what are the effects of syntax evidence (adillah al-nahwu) in grammatical rules. The purposes of the research are to find out the syntax evidence (adillah al-nahwu) in the book Syarh  Kitab al-Kawakib al-durriyah ?ala Mutamammimah al-Ajrumiyyah  and to explain the evidence of syntax (adillah al-nahwu)  found in it?s book,  and to know the effects of the evidence of syntax (adillah al-nahwu)  in the grammar rules. This research used library  research where the data were collected through   document analysis. The results of the research that the most adillah   that used Ar-Ru?ainiy  were  sama?  or  naql, ijma?, and Hadith.   Dalil al-Sama?  of the Qur'an used in the book Syarh  Kitab al-Kawakib al-Durriyah ?ala Mutamammimah al-Ajrumiyyah  were 102  evidences,  dalil  of Hadith were 12 evidences,   dalil  of the words of the Arabs were  60 evidences,  1 dalil of  ijma? , and 4  dalil of istishab al-hal. The syntax evidence (adillah al-nahwu) in the book Syarh  Kitab al-Kawakib al-Durriyah ?ala Mutamammimah al-Ajrumiyyah  affect on availability  for   the understanding of the grammar rules.